A Survey on Information Retrieval Models in Document Mining - R. Meera, R (International Journal of Computer Sciences and Engineering, 2025)
Information retrieval is the process of retrieving relevant documents for the given query over a large document collection. As the technology emergence of digital library and electronic information exchange there is a clear need for organizing and accessing the large quantity of information. Information retrieval focus on the study of storing, organizing and retrieving the information from this large collection. This paper focuses on the types of information retrieval, different fundamental retrieval models and also gives brief overview on document processing